2022
DOI: 10.3390/d14050346
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into a Mediterranean Sea Benthic Habitat: High Diversity of Epiphytic Bryozoan Assemblages on Phyllophora crispa (Rhodophyta) Mats

Abstract: With its geographically isolated location and geological history, the Mediterranean Sea harbors well-known biodiversity hotspots, such as Posidonia oceanica seagrass meadows. Recently, long-living mats formed by the fleshy red alga Phyllophora crispa have been described to be associated with a high diversity of sessile invertebrates in the Tyrrhenian Sea. One of the key taxa among these sessile invertebrates are bryozoans: their abundance, diversity, and spatial distribution in P. crispa mats represent a gap i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…An amount of 41 bryozoan and 5 serpulid species (with 220 colonies and 58 specimens) were present on further algae, largely represented by fronds of Phyllophora crispa. Whereas no data is available for epibionts on F. petiolata, extensive surveys on epibionts growing on P. crispa from several samples collected in different sites and seasons around the Giglio Island (Tuscany Archipelago, NE Tyrrhenian Sea) allowed (Rossbach et al, 2022 [47]) to recognize a number of bryozoan species belonging to 43 different families and ( [47] and Rossbach et al, 2021 [48]) to list 9 serpulid taxa, roughly comparable to figures observed in the present study. As far as we know, together with the record of 54 bryozoan epibiont species on 100 fronds of the large-sized Laminaria rodriguezii Bornet, 1888 (colonisable surface of ca.…”
Section: Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…An amount of 41 bryozoan and 5 serpulid species (with 220 colonies and 58 specimens) were present on further algae, largely represented by fronds of Phyllophora crispa. Whereas no data is available for epibionts on F. petiolata, extensive surveys on epibionts growing on P. crispa from several samples collected in different sites and seasons around the Giglio Island (Tuscany Archipelago, NE Tyrrhenian Sea) allowed (Rossbach et al, 2022 [47]) to recognize a number of bryozoan species belonging to 43 different families and ( [47] and Rossbach et al, 2021 [48]) to list 9 serpulid taxa, roughly comparable to figures observed in the present study. As far as we know, together with the record of 54 bryozoan epibiont species on 100 fronds of the large-sized Laminaria rodriguezii Bornet, 1888 (colonisable surface of ca.…”
Section: Diversitymentioning
confidence: 99%
“…Indeed, few studies have been so far devoted at investigating epibiont communities on habitat-forming bryozoans in general, unlike for other taxa, especially P. oceanica (e.g., Mazzella et al, 1989 [64]; Nesti et al, 2009 [65]; Di Martino and Taylor, 2014 [66] for a review about bryozoan epibionts), some fleshy algae (e.g., [47,50]; Di Geronimo et al, 1990 [67]) and reef-forming organisms, including coralligenous algae and mesophotic benthic animals (e.g., [24] Harmelin, 2017 [68]; Giampaoletti et al, 2020 [69]; Pica et al, 2022 [70], focusing particularly on bryozoans). In European seas, the most investigated species is possibly F. foliacea.…”
Section: Bryozoan and Serpulid Assemblages On M Cereoides And Other L...mentioning
confidence: 99%